MENANAMKAN NILAI-NILAI ANTI KORUPSI MELALUI GURU PENDIDIKAN KEWARGANEGARAAN - asep sjamsul bachri (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2022)
This research generally aims to describe and analyze in depth the implementation of anti-corruption education in schools through the efforts of Civics teachers in instilling anti-corruption values ​​in students. This research is located in SMK Negeri 15 Bandung. The research subjects are class X teachers and class X students. The research process uses a qualitative approach with descriptive methods with data collection techniques in the form of observations, interviews, literature studies, and documentation studies. In this research, data processing and analysis are carried out through the process of compiling, categorizing data, looking for content relationships from various data obtained with the intention of getting their meaning. This research is based on education theory (Ki Hajar Dewantara), corruption theory (M Dawan Rahardjo), and civic education studies (Kaelan). The results showed that (1) the form of learning planning prepared by Civics teachers regarding anti-corruption education at SMK Negeri 15 Bandung had applied good values ​​in accordance with the formation of student character (2) the form of learning implementation prepared by Civics teachers regarding anti-corruption education. corruption in SMK Negeri 15 Bandung has implemented positive and normative values ​​in the material and form of the honesty canteen implementation program (3) the role of Civics teachers in assessing the learning outcomes of anti-corruption behavior of students at SMK Negeri 15 Bandung has implemented the cultivation of an honest, trustworthy attitude , responsible, and steadfast in his stance. Civics teachers are expected to be pioneers in anti-corruption behavior. Thus, anti-corruption education can be integrated through Civics subjects.